What differentiates firms led by female CEOs? - Balasubramanian Elango; Jim Jones; Pat Healey; Bertha Assan-Sackey (Journal of Applied Leadership and Management, 2021)
Research questions: This paper seeks to show what factors differentiate the gender of the CEO in property-casualty insurance firms. Methods: The sample is drawn from firms operating in the United States property-casualty insurance sector. Logistic models are used to differentiate firms led by female CEOs. Results: Results indicate that firms led by female CEOs are likely to be listed publicly, tend to be smaller and hold lower risk, even after controlling for performance and other firm differences.
Keywords: 650